سلوك صفائح القص الفولاذية المختلطة الجدارية تحت تأثير تحميل دوري (Damascus University Journal for engineering sciences, 2023)
Shear walls are considered one of the most structural systems used to resist lateral loadings basically, due to its high shear strength and high lateral stiffness in its plane. Nevertheless, it has low ductile behavior under such loadings. In recent years, research on seismic behavior of composite steel-concrete shear walls has increased. The most important concepts in seismic behavior of structures are strength, ductility, and energy dissipation capacity. This research presents an analytical study by ABAQUS program for composite shear panels to understand its seismic behavior under cyclic loading. The studied-composite shear panels consist of steel plate placed within steel frame and connected from one side with reinforced concrete wall by shear bolts. A gap is introduced between the steel frame and the reinforced concrete wall which surround the steel plate. Before the parametric study, the analytical model is calibrated with experimental model so that satisfactorily close to experimental results are obtained from the analytical model. After that the parametric study included varying the characteristic strength of concrete, thickness of R/C wall, thickness of steel plate, yield strength of steel plate, and spacing between shear bolts. Results obtained by this study included varying thickness of steel plate has the largest effect on improving strength, stiffness, and ductility of composite shear panels. While varying the spacing between shear bolts is the most influential parameter on energy dissipation quantity and the ductility.
Keywords: Composite shear walls; Lateral stiffness; Seismic behavior; Ductility; Energy dissipation; Cyclic loading